2006
DOI: 10.1105/tpc.106.042200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profiling Reveals That Only a Small Number of Phytochrome-Regulated Early-Response Genes inArabidopsisAre Necessary for Optimal Deetiolation

Abstract: In previous time-resolved microarray-based expression profiling, we identified 32 genes encoding putative transcription factors, signaling components, and unknown proteins that are rapidly and robustly induced by phytochrome (phy)-mediated light signals. Postulating that they are the most likely to be direct targets of phy signaling and to function in the primary phy regulatory circuitry, we examined the impact of targeted mutations in these genes on the phy-induced seedling deetiolation process in Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 75 publications
6
125
0
Order By: Relevance
“…1E). These data are consistent with the conclusions from a previous study, where it was found that a large percentage of loss-of-function mutations in single genes implicated in light signaling do not result in any significant defects in deetiolation (Khanna et al, 2006). Here, we show that overexpression of BBX32 resulted in seedlings with elongated hypocotyls along with smaller cotyledons, consistent with phenotypes linked to an altered photomorphogenic response.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…1E). These data are consistent with the conclusions from a previous study, where it was found that a large percentage of loss-of-function mutations in single genes implicated in light signaling do not result in any significant defects in deetiolation (Khanna et al, 2006). Here, we show that overexpression of BBX32 resulted in seedlings with elongated hypocotyls along with smaller cotyledons, consistent with phenotypes linked to an altered photomorphogenic response.…”
Section: Resultssupporting
confidence: 82%
“…For plate-based assays, seeds were sterilized and grown on plates containing growth medium without Suc as described (Khanna et al, 2006). An E-30LED plant growth chamber (Percival) was used for red, far-red, and blue light treatments, and an AR75L chamber (Percival) was used for white light.…”
Section: Plant Growth Conditionsmentioning
confidence: 99%
“…Deetiolation is an excellent model process to study differential light effects on various organs. Although certain organ-specific light-regulated genes have already been identified (8)(9)(10), the core components and molecular mechanisms connecting signals to development were lacking. In our study, by analyzing light-responsive genes in cotyledons and hypocotyls separately, we identified a group of lirSAURs that were oppositely regulated by light in these two organs and that might play key roles in the differential light regulation of various organs (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, the Arabidopsis tubulin gene TUB1 was demonstrated to be down-regulated by light specifically in hypocotyls (8). Mutants affected in several phytochrome-regulated early light response genes exhibited phenotypic differences only in hypocotyls, which indicated that these genes had specific functions in these organs (9). Microarray analysis of dissected organs from Arabidopsis seedlings grown in the dark or in white light found that the expression of hundreds of light-responsive genes was specific to certain organs (10).…”
mentioning
confidence: 99%
“…61 The homolog of BBX24, BBX25, has been reported to function as a negative regulator of hypocotyl elongation under red and farred light. 39,62 The phenotype described for bbx25 mutants is weak, insights on the probable relation of the members to the major regulators of photomorphogenesis and light signaling.…”
Section: The Bbx Subfamily IVmentioning
confidence: 99%